The microbial landscape of tumors: a deep dive into intratumoral microbiota - Sajjad Asgharzadeh; Maryam Pourhajibagher; Abbas Bahador (Frontiers in Microbiology)
Microorganisms in the human body play crucial roles in various health and disease processes. Research indicates that diverse bacterial species are implicated in numerous cancer types. Apart from its involvement in cancer initiation and progression, the microbiome holds promise as a biomarker for diagnosing cancer, assessing risk, and determining prognosis. Intratumoral microbes profoundly impact tumor biology by regulating the initiation and progression of tumors and modulating their response to chemotherapy, radiotherapy, and immunotherapy. A deeper understanding of the role of the intratumoral microbiome in cancer requires further investigation into its effects and underlying mechanisms. This review delves into the significance of intratumoral bacteria in cancer initiation, progression, and metastasis, their impact on cancer treatment outcomes, and Approaches Employed for Profiling the Intratumoral Microbiome.